Titanium Dioxide-Curcumin Composite Materials from Aceh Curcuma Natural Source and Their Evaluation as Antiradical Agents Through In Vitro Study - Vina Aida Roza; Yehezkiel Steven Kurniawan; Indriana Kartini; Tutik Dwi Wahyuningsih; Adhi Dwi Hatmanto (Universitas Gadjah Mada, 2023)
The usage of antiradical agents is pivotal for suppressing the negative effects of free radicals on human health. Curcumin, a well-known natural antiradical agent, suffers from its low stability and high price, thus, limiting its potential in real applications. In this work, we carried out the impregnation of encapsulated curcumin from Aceh curcuma source on commercial titanium dioxide. The isolation of curcumin was performed using a simple maceration method, while the encapsulation process was done employing carboxymethylcellulose and maltodextrin to give ethanol-curcumin and triacetin-curcumin powders in 30.35% and 37.21% yield, respectively. The composite materials contained curcumin in a range of 0.016–0.374 mg/g. The characterization data revealed that the curcumin was located on the surface of titanium dioxide through hydrogen bonds. The in vitro DPPH assay of the titanium dioxide-curcumin composite material exhibited 39.61 ± 1.36 to 79.70 ± 1.33% antiradical activity which was higher than titanium dioxide (31.78 ± 1.48%). Furthermore, the composite material also gave higher antiradical activity than its curcumin sources, i.e., Aceh curcuma (75.12 ± 1.79%), ethanol-curcumin (56.66 ± 0.25%), and triacetin-curcumin (63.58 ± 0.20%) demonstrating a synergistic antiradical effect of titanium dioxide and curcumin as the antiradical agents. These findings demonstrate the importance of the impregnation and encapsulation of curcumin in composite materials for antiradical applications.